Hydrogen peroxide release by bacteria suppresses inflammasome-dependent innate immunity - Saskia F. Erttmann (Nature Portfolio, 2019)
The functions of microbial hydrogen peroxide (H2O2) in host-pathogen interactions are unclear. Here, Erttmann and Gekara show that H2O2 released by Streptococcus pneumoniae inhibits inflammasomes, and thereby contributes to the pathogen’s ability to colonize the host.